2009
DOI: 10.4049/jimmunol.0900903
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Preexisting MAGE-A3-Specific CD4+ T Cells in Cancer Patients and Healthy Individuals and Their Activation by Protein Vaccination

Abstract: Vaccination with cancer/testis Ag MAGE-A3 in the form of recombinant protein often induces specific humoral and cellular immune responses. Although Ag-specific CD4+ T cells following vaccination are detectable by cytokine production after a single in vitro stimulation, their detection before vaccination is difficult because of low frequency. In this study, we have applied a sensitive method using CD154 (CD40L) staining to detect MAGE-A3-specific CD4+ T cells. MAGE-A3-specific T cell responses were analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…These results indicated that OLP-alone vaccination selectively deleted or anergized high-avidity precursors. A similar observation was made in patients vaccinated with MAGE-A3 protein alone in comparison with patients vaccinated with MAGE-A3 in the adjuvant system AS02B, indicating that this phenomenon is not limited to peptide vaccination (18). Interestingly, patients who received MAGE-A3 protein alone did not respond to booster vaccinations with MAGE-A3þAS02B adjuvant, indicating that deletion or persistent anergy of high-avidity CD4 þ T cells led to long-term tolerance (27,28 (35).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…These results indicated that OLP-alone vaccination selectively deleted or anergized high-avidity precursors. A similar observation was made in patients vaccinated with MAGE-A3 protein alone in comparison with patients vaccinated with MAGE-A3 in the adjuvant system AS02B, indicating that this phenomenon is not limited to peptide vaccination (18). Interestingly, patients who received MAGE-A3 protein alone did not respond to booster vaccinations with MAGE-A3þAS02B adjuvant, indicating that deletion or persistent anergy of high-avidity CD4 þ T cells led to long-term tolerance (27,28 (35).…”
Section: Discussionsupporting
confidence: 62%
“…To investigate the effects of Montanide and poly-ICLC in the differential immunogenicity of OLP, we addressed the quantitative and qualitative changes in vaccine-induced NY-ESO-1-specific CD4 þ T cells depending on vaccine compositions using an in-depth sensitive approach. As we reported previously, upregulation of CD154 (CD40-ligand) on CD4 þ T cells restimulated with tumor antigen peptides after a single in vitro peptide sensitization was used successfully to isolate tumor antigen-specific CD4 þ T cells (18). CD154 upregulation is sufficiently sensitive to allow the isolation of low-frequency tumor antigen-specific CD4 þ T-cell precursors even from healthy donors or from patients before vaccination.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…1A). Next, we established NY-ESO-1-specific CD4 + Tcell lines in a subset of ovarian cancer patients pre-and postvaccination, as previously described (9). We determined Th1, Th2, and Th17 differentiation based on IFN-γ, IL-4, IL-13, or IL-17 production upon stimulation with NY-ESO-1 pooled peptides.…”
Section: Impact Of Rv-ny-eso-1 and Rf-ny-eso-1 Vaccination On Progresmentioning
confidence: 99%
“…CD4 + T cells, and peptide-pulsed T celldepleted PBMCs were cocultured for 20 d in the presence of 10 U/ml IL-2 (Roche Diagnostics) and 20 ng/ml IL-7 (R&D Systems) to allow expansion of NY-ESO-1-specific CD4 + T cells. NY-ESO-1 peptide-specific T cell lines were established as described (15). CD154-expressing CD4 + T cells were isolated after restimulation with PHA-activated CD4 + T cells (T-APC) pulsed with a subpool (#9-#12 peptides) of NY-ESO-1 overlapping peptides using a FACSAria instrument and expanded with PHA (Remel).…”
Section: Generation Of Ny-eso-1-specific Cd4 + T Cell Linesmentioning
confidence: 99%